2017
DOI: 10.1103/physreve.96.022706
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field-induced shape transition of nematic tactoids

Abstract: The occurrence of new textures of liquid crystals is an important factor in tuning their optical and photonics properties. Here, we show, both experimentally and by numerical computation, that under an electric field chitin tactoids (i.e. nematic droplets) can stretch to aspect ratios of more than 15, leading to a transition from a spindle-like to a cigar-like shape. We argue that the large extensions occur because the elastic contribution to the free energy is dominated by the anchoring. We demonstrate that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 45 publications
10
44
0
Order By: Relevance
“…1; negative Z values) two þ1=2 defects localize at each pole and, unlike in extensile systems, self-propel towards their cometlike tails, stretching the initially spherical shell into a spindle shape. The spindle configuration of the shells resembles the tactoids formed in lyotropic liquid crystals [28,31,32] and in recently reported droplets of actin filaments [17]. Increasing the contractile activity first further elongates the spindles.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…1; negative Z values) two þ1=2 defects localize at each pole and, unlike in extensile systems, self-propel towards their cometlike tails, stretching the initially spherical shell into a spindle shape. The spindle configuration of the shells resembles the tactoids formed in lyotropic liquid crystals [28,31,32] and in recently reported droplets of actin filaments [17]. Increasing the contractile activity first further elongates the spindles.…”
supporting
confidence: 63%
“…The bulk free energy is further complemented by the Frank elastic energy F elastic ¼ ðL=2Þð∇QÞ 2 , penalizing orientational deformations, and an interfacial anchoring free energy F anchoring ¼ L 0 ∇ϕ • Q • ∇ϕ, with L 0 > 0 to ensure that the director field lies parallel to the interface. Using this free energy description, we can write the passive stress tensor in terms of viscous, elastic, and capillary contributions, as in previous work [28], but now including two additional terms because of the appearance of ∇ 2 ϕ in the membrane free energy: ∇ϕ∇ð∂F =∂∇ 2 ϕÞ − ∇∇ϕð∂F =∂∇ 2 ϕÞ. In addition to the passive stresses, the active stress is defined as Σ active ¼ −ζQ such that gradients in the orientational order Q generate active forces that drive active flows.…”
mentioning
confidence: 99%
“…Correspondingly, tactoids can be created by intense laser heating and controlled by electric or magnetic fields. It was reported that tactoids can be reversibly aligned and stretched by up to a factor of fifteen in length using an electrical field [55]. Our findings suggest that an array of tactoids created on demand can be used to capture negative defects and thus create a positively charged active nematic liquid.…”
Section: Discussionmentioning
confidence: 55%
“…In the present section, we generalize the phenomenological model of Weirich et al [8] to explain our results. We will work within the bipolar tactoid model [24,32] which has been invoked to explain tactoid shape trends in numerous experiments [33][34][35][36][37][38][39], as well as simulations [40,41], and which our simulated tactoids also resemble. We then discuss our results in a broader context, and describe a set of minimal extensions beyond the simulation models used here that may allow for the realization of stably divided tactoids.…”
Section: Discussionmentioning
confidence: 99%